G232(P) Youth on youth violence: the scale of the problem. (27th April 2016) - Taylor, C; Leith, L; Hannon, F; Potter, S; Hann, G
Abstract : Background: Youth on youth violence is a serious problem in many areas of England. Gangs have a significant impact on the communities they operate within. Research has shown that violence is a key factor in desistance from gangs, so identifying those involved at presentation to A&E is vital. Aims: Local police statistics for 2013–14 has shown knife crime has increased by 40% in our borough compared to 4% across London. We aimed to see if this rise was matched by presentations to A&E for gang violence. We also aimed to map the demographics and injuries of those presenting with assaults. Method: A manual notes review of all A&E cards was performed during a 3 month period from September to December 2014. A comparison with local police crime statistics showed that this was a 'quieter' time for youth violence which tends to peak in summer months. Injuries in the 12–24 year olds were identified and data collected on age, gender, history given and injury type. Results: There were 42, 306 presentations to A&E in the study timeframe. 1, 522 injuries were identified in the 12–24 year olds. 10% (156) of these injuries were categorised as assaults. 56% of presentations were for those aged 12–15 years, with the most injuries occurring in 12 year olds. Overall the male:female ratio for injuries was 2:1 with males representing 71% of assaults. The attacker's body was the most common weapon with 24% being punched and 12% being kicked and punched. Other modes of assault were kicks, bites and sexual assaults. When weapons were documented, knives were used in 12% of cases, followed by baseball bats, bottles, glass, hammers and metal bars. One third of victims suffered injuries to multiple sites reflecting that in 22% of cases a 'group' or 'gang' were reported as the assailants. Conclusion: This study clearly demonstrates that in a 'quiet' month for police reports, there is a significant number of young people requiring treatment for gang violence. This data has provided evidence for a youth worker funded by the Mayor's Office for Policing and Crime and we will be assessing the impact of this provision.